Incidencia del maltrato en el rendimiento académico de los estudiantes del sexto y séptimo año de educación básica de la Escuela Rómulo Vidal de la ciudad de Machala durante el período 2012-2013. - Rodríguez Gonzáles, Jislaine Elizabeth (2013)
The study is descriptive, with the help of the surveys, the survey data variables was performed, general characteristics of the study population and situation of abuse in children to assess the type of child abuse.